The Potency of Local Bacterial Isolates Encapsulated Within Sodium Alginate in Carbofuran Degradation. (March 2018) - Priyani, Nunuk; Pratiwi, Dian; Suryanto, Dwi
Abstract: Research on the viability of bacteria encapsulated within sodium alginate and their potential in carbofuran degradation has been done. A total of 8 bacterial isolates have been isolated from slaughter house waste. A 100 ml of Bushnell-Hass Broth (BHB) medium containing 146.982 ppm of carbofuran was used as a medium. As much as 2 gr of beads which equal to 10 8 cells.ml −1 was inoculated into each medium culture and incubated for 15 days at ambient temperature and was shaken at 100 rpm. Analysis of carbofuran residues using High Performance Liquid Chromatography (HPLC) showed that the best 2 isolates, DN 1 and OR 2, were able to decrease carbofuran phenol concentration up to 30.37 % and 32.09% respectively compared to control. These results suggested that no significant different from the ability of free cell which decreased carbofuran phenol concentration up to 32.54% and 28.29%.